Expanded CUG repeat RNAs form hairpins that activate the double-stranded RNA-dependent protein kinase PKR. - Tian, B (2000)
Myotonic dystrophy is caused by an expanded CTG repeat in the 3' untranslated region of the DM protein kinase (DMPK) gene. The expanded repeat triggers the nuclear retention of mutant DMPK transcripts, but the resulting underexpression of DMPK probably does not fully account for the severe phenotype. One proposed disease mechanism is that nuclear accumulation of expanded CUG repeats may interfere with nuclear function. Here we show by thermal melting and nuclease digestion studies that CUG repeats form highly stable hairpins. Furthermore, CUG repeats bind to the dsRNA-binding domain of PKR, the dsRNA-activated protein kinase. The threshold for binding to PKR is approximately 15 CUG repeats, and the affinity increases with longer repeat lengths. Finally, CUG repeats that are pathologically expanded can activate PKR in vitro. These results raise the possibility that the disease mechanism could be, in part, a gain of function by mutant DMPK transcripts that involves sequestration or activation of dsRNA binding proteins.